Question and Answers Forum

All Questions      Topic List

Differentiation Questions

Previous in All Question      Next in All Question      

Previous in Differentiation      Next in Differentiation      

Question Number 84442 by Power last updated on 13/Mar/20

Answered by john santu last updated on 13/Mar/20

let y = x^(3x^(5x) )  ⇒ln(y)= ln(x^(3x^(5x) ) )  let 3x^(5x)  = g(x)  ⇒ ln(y)= ln(x^(g(x)) )   ⇒ln(y) = g(x) ln(x)  ⇒((y ′)/y) = ((g(x))/x) + g ′(x)ln(x)  now consider g(x)= 3x^(5x)   ln(g(x)) = ln(3x^(5x) ) = ln(3)+5x ln(x)  ((g ′(x))/(g(x))) = 0+((5x)/x)+5ln(x)  ((g ′(x))/(g(x)))= 5ln(ex) = ln(ex)^5   g ′(x)= 15x^(5x)  ln(ex)  now y′ = y [3x^(5x−1) +15xln(ex)ln(x) ]  y ′ =x^(3x^(5x) )  [ 3x^(5x−1)  + 15xln(ex) ln(x) ]

$$\mathrm{let}\:\mathrm{y}\:=\:\mathrm{x}^{\mathrm{3x}^{\mathrm{5x}} } \:\Rightarrow\mathrm{ln}\left(\mathrm{y}\right)=\:\mathrm{ln}\left(\mathrm{x}^{\mathrm{3x}^{\mathrm{5x}} } \right) \\ $$$$\mathrm{let}\:\mathrm{3x}^{\mathrm{5x}} \:=\:\mathrm{g}\left(\mathrm{x}\right) \\ $$$$\Rightarrow\:\mathrm{ln}\left(\mathrm{y}\right)=\:\mathrm{ln}\left(\mathrm{x}^{\mathrm{g}\left(\mathrm{x}\right)} \right)\: \\ $$$$\Rightarrow\mathrm{ln}\left(\mathrm{y}\right)\:=\:\mathrm{g}\left(\mathrm{x}\right)\:\mathrm{ln}\left(\mathrm{x}\right) \\ $$$$\Rightarrow\frac{\mathrm{y}\:'}{\mathrm{y}}\:=\:\frac{\mathrm{g}\left(\mathrm{x}\right)}{\mathrm{x}}\:+\:\mathrm{g}\:'\left(\mathrm{x}\right)\mathrm{ln}\left(\mathrm{x}\right) \\ $$$$\mathrm{now}\:\mathrm{consider}\:\mathrm{g}\left(\mathrm{x}\right)=\:\mathrm{3x}^{\mathrm{5x}} \\ $$$$\mathrm{ln}\left(\mathrm{g}\left(\mathrm{x}\right)\right)\:=\:\mathrm{ln}\left(\mathrm{3x}^{\mathrm{5x}} \right)\:=\:\mathrm{ln}\left(\mathrm{3}\right)+\mathrm{5x}\:\mathrm{ln}\left(\mathrm{x}\right) \\ $$$$\frac{\mathrm{g}\:'\left(\mathrm{x}\right)}{\mathrm{g}\left(\mathrm{x}\right)}\:=\:\mathrm{0}+\frac{\mathrm{5x}}{\mathrm{x}}+\mathrm{5ln}\left(\mathrm{x}\right) \\ $$$$\frac{\mathrm{g}\:'\left(\mathrm{x}\right)}{\mathrm{g}\left(\mathrm{x}\right)}=\:\mathrm{5ln}\left(\mathrm{ex}\right)\:=\:\mathrm{ln}\left(\mathrm{ex}\right)^{\mathrm{5}} \\ $$$$\mathrm{g}\:'\left(\mathrm{x}\right)=\:\mathrm{15x}^{\mathrm{5x}} \:\mathrm{ln}\left(\mathrm{ex}\right) \\ $$$$\mathrm{now}\:\mathrm{y}'\:=\:\mathrm{y}\:\left[\mathrm{3x}^{\mathrm{5x}−\mathrm{1}} +\mathrm{15xln}\left(\mathrm{ex}\right)\mathrm{ln}\left(\mathrm{x}\right)\:\right] \\ $$$$\mathrm{y}\:'\:=\mathrm{x}^{\mathrm{3x}^{\mathrm{5x}} } \:\left[\:\mathrm{3x}^{\mathrm{5x}−\mathrm{1}} \:+\:\mathrm{15xln}\left(\mathrm{ex}\right)\:\mathrm{ln}\left(\mathrm{x}\right)\:\right] \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com